(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, it is researched that building an enlightened society is the basis of educating an enlightened person. It is revealed that the formation of an enlightened society is connected with the need for the formation of enlightenment. It has been studied that education is one of the main factors of the stability of an enlightened society.